Photodynamic diagnosis and therapy of epithelial vulvar diseases - Olejek, Anita; Rembielak-Stawecka, Beata; Kozak-Darmas, Iwona (Menopause Review/Przegląd Menopauzalny, 2005)
Photodynamic method is a new technique with unique properties that make it attractive for treatment of vulvar epithelial disorders. Authors describe photodynamic method in their own studies: diagnosis and treatment of lichen sclerosus and diagnosis of vulvar intraepithelial neoplasia and condylomata accuminata vulvae. 42 patients were treated with histopathological diagnosis of lichen sclerosus. 2., 5 hours after topical application of 20% 5-ALA, photodynamic diagnosis was conduced. Afterwards all the areas were irradiated with semiconductor laser, energy dose 120 J/cm 2 , fluence rate 400 mW/cm 2 . Patients underwent 3-6 cycles PDT in 2 weeks intervals. 2-4 weeks after last therapy patients underwent clinical, photodynamic and histopathological verification. 14 patients with VIN had 10% ALA applied to the entire vulva. 1 hour after drug application the vulva was examinated in white light and in fluorescence light at a wavelength of 442 nm. Next, 13 patients were treated by surgical excision and the histopathological character of the resected tissues was established. Photodynamic method using 5-ALA represents an alternative treatment method for lichen sclerosus and has the advantage of minimal tissue destruction, low side effects and excellent cosmetic results.